Erythrocyte levels of n-3 polyunsaturated fatty acids and incidence of frailty after a 6-year follow-up: the Korean frailty and aging cohort study - Kim, Jueun; Kim, Miji; Won, Chang Won; Park, Yongsoon (Frontiers in Nutrition, 2025)
Previous studies have shown that the blood levels of n-3 polyunsaturated fatty acids (PUFA) are inversely associated with the prevalence of frailty, but associations with frailty incidence remain unknown. We examined the hypothesis that the erythrocyte levels of n-3 PUFA such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are inversely associated with the incidence of frailty after a 6-year follow-up. Using the Korean Frailty and Aging Cohort Study data, 1,119 community-dwelling Korean participants aged 70–84 years without frailty were observed for 6 years. Frailty was defined using the Cardiovascular Health Study index. In the multivariable adjusted model, the incidence of frailty was 11.1% after a 6-year follow-up and inversely associated with the Omega-3 Index (sum of EPA + DHA) (HR: 0.47; 95% CI: 0.27–0.84; P for trend = 0.005), and DHA levels (HR: 0.36; 95% CI: 0.19–0.68; P for trend = 0.003). Regarding frailty components, the incidence of low physical activity, slow walking speed, and weight loss were inversely associated with the Omega-3 Index and DHA levels. The Omega-3 Index (p = 0.043) and DHA levels (p = 0.019) differed significantly among the frailty transition groups (persistence, reversal, and deterioration). All-cause mortality was inversely associated with the Omega-3 Index (p = 0.011), and EPA (p = 0.012) and DHA levels (p = 0.032). The incidence of frailty was inversely associated with the Omega-3 Index and erythrocyte DHA levels, suggesting that interventions with n-3 PUFA are beneficial for preventing the progression of frailty and mortality among community-dwelling older adults in Korea.